As Deusas dos Ramos e o Sagrado Feminino - Damm, Camila Goos [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
No conjunto de lendas galesas intitulado O Mabinogion (séc. XIV-XV) encontram-se histórias que remetem ao passado pagão das tribos celtas que habitavam a Grã-Bretanha, registradas e modificadas após o processo de cristianização e a influência da estética medieval. O presente trabalho analisa três de suas proeminentes personagens femininas que provavelmente um dia possuíram status divino, Rhiannon, Aranrhod e Blodeuwedd, a partir tanto do estudo da cultura celta quanto dos arquétipos sob a perspectiva junguiana. Através dessas análises, discute-se conceitos e interpretações do sagrado feminino, da construção da inferioridade social feminina e do papel do mito e das artes na revisão e reconstrução dessa identidade, dialogando com os estudos feministas.

In the group of Welsh legends called The Mabinogion (XIV-XV centuries) are found stories that relate to the pagan past of the Celtic tribes that inhabited Great Britain, registered and modified after the process of Christianisation and the influence of medieval aesthetics. This dissertation analyses three of its prominent female characters that probably once had divine status, Rhiannon, Aranrhod and Blodeuwedd, considering both the characteristics of Celtic culture and the study of the archetypes in Jungian perspective. Through these analyses, concepts and interpretations for the sacred feminine, the construction of female’s social inferiority and the part myhts and art can play at the revision and reconstruction of this identity are discussed, dialoguing with feminist studies.
The godesses of the branches and the sacred feminine
Keywords: Mabinogion; arquétipos; sagrado feminino; feminismo; mitologia celta; celtic mythology; sacred feminine; feminism; archetypes